Historical Study Of The Tomb Of Raja Raja Sigam Of Sea Island 1855-1900 In The Wetland Area Of Sigam Sea Island Kotabaru District - Effendi*, Rusdi; Yahya, Daud (Universitas Syiah Kuala, 2024)
Indonesia has many historical relics that are the legacy of our ancestors. These historical relics are priceless wealth, which really need to be cared for and utilized as well as possible. The purpose of this research is to analyze the Historical Study of the Tombs of the Kings of Sigam Sea Island 1855-1900 in the Wetland Area of Sigam Sea Island, Kotabaru Regency. The method used in the research uses historical methods consisting of heuristics, criticism, interpretation, and historiography. The results show that the Sigam tomb complex consists of three cupola buildings, each of which contains more than one tombstone. The cupola buildings were newly built to store the tombs of kings and princes who once ruled Laut Island. Inside the cupola buildings are the tombs of the king and his highly respected family members, while other tombs of the king's relatives are scattered outside the cupola buildings without a clear pattern.